The effects of an individualized exercise intervention on body composition in breast cancer patients undergoing treatment - Battaglini, Claudio; Bottaro, Martim; Dennehy, Carolyn; Rae, Logan; Shields, Edgar; Kirk, David; Hackney, Anthony (São Paulo Medical Journal, 2007)
CONTEXT AND OBJECTIVE: Changes in metabolism have been reported in the majority of patients undergoing cancer treatment, and these are usually characterized by progressive change in body composition. The effects of aerobic exercise programs to combat the cancer and cancer treatment-related side effects, which include the negative changes in body composition, have been extensively reported in the literature. However, few resistance exercise intervention studies have hypothesized that breast cancer patients might benefi t from this type of exercise. The purpose of this study was to determine whether exercise protocols that emphasize resistance training would change body composition and strength in breast cancer patients undergoing treatment. DESIGN AND SETTING: Randomized controlled trial, at the Campus Recreation Center and Rocky Mountain Cancer Rehabilitation Institute of the University of Northern Colorado, and the North Colorado Medical Center. METHODS: Twenty inactive breast cancer patients were randomly assigned to a 21-week exercise group (n = 10) or a control group (n = 10). The exercise group trained at low to moderate intensity for 60 minutes on two days/week. The primary outcome measurements included body composition (skinfold method) and muscle strength (one repetition maximum). RESULTS: Signifi cant differences in lean body mass, body fat and strength (p = 0.004, p = 0.004, p = 0.025, respectively) were observed between the groups at the end of the study. CONCLUSION: The results suggest that exercise emphasizing resistance training promotes positive changes in body composition and strength in breast cancer patients undergoing treatment.